Global effect - Walker, Cynthia Garcia; Cunningham, Terry ([United States] : DEJ Productions, Inc., 2003)
His name is Miles Spencer, and he's the new face of global terror. His goal is to cleanse the planet of the unwanted, and he's found the perfect weapon - the deadliest virus known to mankind. Now, the race is on to find one man ... or humanity will face total destruction
Executive producer, Vicki L. Sawyer ; writer, Terry Cunningham
Cast: Madchen Amick, Daniel Bernhardt, Joe West, Arnold Vosloo
VCD format
Keywords: Death in motion pictures; Murder in motion pictures